Kesan peraturan baru ke atas kelewatan audit laporan kewangan: kajian ke atas pasaran Ace, Malaysia - Mohamad Hisyam, Baharom (2018)
This paper analyses the impact of new regulation on audit delays. Audit delays are measured by the numbers of days that elapse from the end of the financial year until the date when the auditor report is signed. Previous studies of audit delays in various countries are reviewed, along with some of the results of the variable tested. This study focuses on 91 companies listed on Bursa Malaysia as at 31 Disember 2015 to 2016. Seven explanatory variables are tested to investigate delays in issuing audit reports. The results show that new regulation, type of auditors and audit complexity are significantly correlates with audit delay in the period tested. Other variables such as size of the company, type of income, leverage and audit opinion show no significant correlation with audit delay. The outcome of the study could support regulatory bodies in the process of drafting new rules in futures and help management to reduce delay. The study therefore, recommended that future studies should include additional corporate governance variables like characteristic of board directors and audit committee.